Foucault, normativity and critique as a practice of the self. - Han-Pile, Béatrice (Continental Philosophy Review, 2016)
In this paper I distinguish between two main critical questions: 'how possible' questions, which look for enabling conditions (empirical or transcendental) and raise issues of epistemic normativity; and 'whether permissible' questions, which relate to conditions of legitimacy and ethical normativity. I examine the interplay of both types of questions in Foucault's work and argue that this helps us to understand both the function of the historical a priori in the archeological period and the subsequent accusations of crypto-normativity levelled against Foucault by commentators such as Taylor and Habermas. I chart the complex conceptual space available for a defense. After examining several possible replies (in particular deflationary and constructivist), I conclude that the most effective option, and the one that fits Foucault's approach best, is to refuse the demand for normative justification as self-defeating, and to opt for the cultivation of an appropriate ethical sensibility through an emphasis on critique as a performative practice of the self. I offer in conclusion some thoughts on what such practice may look like for Foucault.